Educational Perspective: AI, Deep Learning, and Creativity - Dainys, Augustinas; Jašinauskas, Linas (Problemos, 2023)
Can artificial intelligence (AI) teach and learn more creatively than humans? The article analyses deep learning theory, which follows a deterministic model of learning, since every intellectual procedure of an artificial agent is supported by concrete neural connections in an artificial neural network. Meanwhile, human creative reasoning follows a non-deterministic model. The article analyses Bayes’ theorem, in which a reasoning system makes judgments about the probability of future events based on events that have happened to it. Meillassoux’s open probability and M. A. Boden’s three types of creativity are discussed. A comparison is made between the a priori algorithm of the Turing machine and a playing child, who invents new a posteriori algorithms while playing. The Heideggerian perspective on the co-creativity of humans and thinking machines is analyzed. The authors conclude that humans have an open horizon for teaching and learning, and that makes them superior with respect to creativity in an educational perspective.